Edukasi “Tuberkulosis Bukan Kutukan” Guna Menurunkan Stigmatisasi TB Ditengah Masyarakat - Ilil Maidatuz Zulfa; Widya Handayani (Jurnal Abdi Masyarakat Kita, 2023)
Tuberculosis (TB) is an infectious disease that still be the leading cause of mortality worldwide. In Indonesia, the success treatment rate still below the standard set by WHO. One of the factors contributed to the success treatment rate is patients medication adherence while the factors affected patients medication adherence are patients knowledge, social support and public stigma. Negative stigma on patients TB could be reduced by public education and campaign. This community service was aimed to educate public in order to eliminate negative stigma on TB patients. A total of 82 participants joined the event. 63 of them had filled the stigma questionnaire. The results showed that there was an increase in number of participants who had positive perpective on TB patients. A continuous campaign and public education will reduce the stigmatitation on TB patients.